FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENYAKIT DIABETES MELITUS TIPE 2 PADA PASIEN DI RUMAH SAKIT GRANDMED LUBUK PAKAM - Reno Irwanto; Annisa Febriana Siregar; Keleng Ate Ginting; Feberlian Ndruru (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2021)
Diabetes mellitus (DM) type 2 is a type of DM which is caused by the inability of the body to process glucose into the body which eventually causes an increase in glucose in the blood. Type 2 diabetes occurs because the amount of the hormone insulin is insufficient for glucose metabolism or decreased body sensitivity to the amount of blood glucose. There are many things that cause type 2 diabetes, including poor diet, lack of physical activity, obesity, heredity, increasing age and a history of type 3 diabetes (gestational). This study was conducted on 50 respondents at the Grandmed Lubuk Pakam hospital with a cross sectional study design and the respondents were selected by purposive sampling technique. The relationship factors seen in this study were age, gender, level of education, occupation, level of education, level of physical activity, smoking, obesity and diet. The results of the research obtained through the questionnaire were tested with the chi-square formula (X2) at the 5% real level. The results showed the distribution of respondents' occupation with 28% of respondents working as civil servants, 22% were retirees and 18% were private workers. The distribution of the respondents' physical activity consists of 3 levels, namely high, medium and low with percentage values ​​of 26%, 22%, and 52%, respectively. The distribution of the respondents' weight group was found that 18% of the respondents were underweight, 46% were normal, and 36% were obese. The test results showed the distribution of the respondent's diet in 2 groups, namely healthy and unhealthy with the percentage of the unhealthy group 66% and 34% healthy. and the distribution of respondents' smoking levels consisted of heavy, moderate, mild and non-smoking with percentage values ​​of 26%, 22%, 12%, and 40%, respectively.